PEMBELAJARAN KOOPERATIF STAD DENGAN STRATEGI PENUGASAN MULTI LEVEL INSTRUCTION PADA MATERI MATEMATIKA - Mahmud, Randy Saputra; Syamsuadi, Ahmad; Nursakiah, Nursakiah (Journal of Honai Math, 2019)
The purpose of this study was to determine the activities, responses, and student learning outcomes with multilevel instruction learning. Multilevel instruction assignment learning strategy is a selling system adoption from multi-level marketing strategy with special characteristics that there are students in theÂ first level and second level downlines and a teacher as an upline. Type of research is quasi-experimental by comparing two experimental groups. Experimental group one was given the STAD model with multilevel instruction, and the other group was given regular STAD model. The research instruments used were student activity observation sheets, student response questionnaires, and learning outcomes test. The data obtained were analyzed descriptively and inferentially. The result indicates that both of them are effective to be applied in mathematics learning, but inferentially the outcomes of the experiment group one were higher than the experiment group two.